MUSLIM MILLENNIAL PERSPECTIVE ON THE EXISTENCE AND CO-EXISTENCE OF RELIGIOUS MINORITIES IN INDONESIA - Jubba, Hasse; Qodir, Zuli; Abdullah, Irwan; Herman,; Pabbajah, Mustaqim; R, Abd Rahman; Iribaram, Suparto (International Journal of Psychosocial Rehabilitation, 2020)
The practice of tolerance in a pluralistic society in terms of religion holds the potential for the birth of a mutually accepting relationship on the one hand, and an attitude of mutual negation on the other. This paper specifically discusses the practice of tolerance among millennial Muslims in Indonesia by looking at the reasons underlying their attitude towards the existence of religious minority groups. Data analyzed are obtained through questionnaires, interviews, and literature studies. Questionnaires distributed to millennial Muslims contain requests to choose choices and write opinions about the existence of minority religious groups. This paper shows two responses to the existence of minority religious groups. First, respondents accept the existence of non-Islamic religious groups (out of 412 respondents, as many as 280 or 67, 96%) for various reasons. Second, most respondents reject the existence of Islamic religious groups, especially Shiites and Ahmadis. In this case, 383 respondents (93%) state their rejection. Both forms of response have their respective reasons. This study recommends the importance of cultivating an attitude of respect for differences so that conflicts based on religion can be avoided in the future.